Fishing and stock fluctuations / Taivo Laevastu - Laevastu, Taivo (Inglaterra: Fishing News Brooks Ltd, 1988)
The ever-changing fishery and our conception of it, diversity of objectives in fisheries and the search for stability; marine environment as determinant of fisheries, coastal or inshore environments and their fish ecosytems; availability of fish to gear, pelagic fish; effects of fishng and optimum take, production processes in fish ecosytems and the recruitment problem.
Contents, table, graph, map
Col. Pesc
Keywords: 1. FISH 2. FISHING FLUCTUATIONS 3. BIOLOGY 4. FISHES